#### Answer

$x=\frac{1}{3}$
$y=\frac{1}{2}$

#### Work Step by Step

If we multiply the first equation by $4$, then we add the two equations, we can eliminate the $y$ from the system:
$3\times4x-2\times4y=0\times4$
$9x+8y=7$
$12x+9x=21x=7$
$x=\frac{1}{3}$
$3(\frac{1}{3})-2y=0$
$y=\frac{1}{2}$
We have to check, if the solution is right. Substitute $x$ with $\frac{1}{3}$ and $y$ with $\frac{1}{2}$:
$3(\frac{1}{3})-2(\frac{1}{2})=1-1=0$ $\checkmark$
$9(\frac{1}{3})+8(\frac{1}{2})=3+4=7$ $\checkmark$